Community Nutrition for Developing Countries (a co-publication with UNISA Press) - Edited by Norman J. Temple and Nelia Steyn (Athabasca University Press, 2016)
Nutrition textbooks used by universities and colleges in developing countries have very often been written by scholars who live and work in North America or the United Kingdom. And while the research and information they present is sound, the nutrition-related health challenges with which developing countries must grapple differ considerably from those found in highly industrialized Western nations. The primary aim of Community Nutrition for Developing Countries is to provide a book that meets the needs of nutritionists and other health professionals living and working in developing countries. Written by both scholars and practitioners, the volume draws on their wealth of knowledge, experience, and understanding of nutrition in developing countries to provide nutrition professionals with all the information they require. Each chapter addresses a specific nutrition challenge currently faced by developing countries such as food security, food safety, disease prevention, maternal health, and effective nutrition policy. In addition, the volume serves as an invaluable resource for those developing and implementing nutrition education programmes. With an emphasis on nutritional education as a means to prevent disease and effectively manage health disorders, it is the hope of the nearly three dozen contributors to this work that it will enhance the health and well-being of low-income populations throughout the world.